How does cloud-radiative heating over the North Atlantic change with grid spacing, convective parameterization, and microphysics scheme in ICON version 2.1.00? - Sylvia Sullivan (Department of Chemical and Environmental Engineering, University of Arizona); Behrooz Keshtgar (Institute of Meteorology and Climate Research, Karlsruhe Institute of Technology); Nicole Albern (Institute of Meteorology and Climate Research, Karlsruhe Institute of Technology); Elzina Bala (Institute of Meteorology and Climate Research, Karlsruhe Institute of Technology); Christoph Braun (Institute of Meteorology and Climate Research, Karlsruhe Institute of Technology); Anubhav Choudhary (Institute of Meteorology and Climate Research, Karlsruhe Institute of Technology); Johannes Hörner (Department of Meteorology and Geophysics, Faculty of Earth Sciences, Geography and Astronomy, University of Vienna); Hilke Lentink (Institute of Meteorology and Climate Research, Karlsruhe Institute of Technology); Georgios Papavasileiou (Institute of Meteorology and Climate Research, Karlsruhe Institute of Technology); Aiko Voigt (Department of Meteorology and Geophysics, Faculty of Earth Sciences, Geography and Astronomy, University of Vienna) (Geoscientific Model Development, 2023)
The abstract is available here: https://uscholar.univie.ac.at/o:2069705 The abstract is available here: https://uscholar.univie.ac.at/o:2069705